Pedagogical conditions of forming librarian’s professional culture - E. A. Kurilenko; N. A. Turanina (Библиосфера, 2017)
This article is devoted to the professional culture of specialists, who work in the librarian information sphere. The diagnostics of professional culture level conducted as anonymous questioning was carried on among the students studying the course 51.03.06 «Librarian information activity» and young librarians, which results have revealed insufficiency of their professional competences. The study purpose is enhancing the professional culture of specialist in the library-information field. The research objectives are: to define the concept «professional culture», to analyze a problem of pedagogical conditions in contemporary science, to substantiate the necessity of introducing new organizational pedagogical conditions in the training process of bachelors - future librarians, to work out an organizational pedagogical condition - a content of training special course aimed to solving the problem of insufficiency of librarians’ professional culture. The authors have suggested an organizational pedagogical condition: introducing a special course «Professional culture of specialist of the librarian-information sphere» in the curriculum of some groups. Its content is designed to develop actively future librarians’ professional culture and to master their theoretical and practical competences. The special course content is based on the recognition of professional culture as universalizable characteristics of various types of library-information activities and library communications that reflect the fullness and diversity of professional interests and needs, value orientations, capabilities and abilities of a librarian professional. Thematic sections of the special course are defined in accordance with modern requirements to the culture of a specialist who fulfills specific kinds of librarian activities: pedagogical, bibliographic, innovative, methodical, communicative, and also librarian information serving, etc.